TINGKAT MUTU HEDONIK BEKASEM IKAN NILA PADA LAMA FERMENTASI YANG BERBEDA - Junianto; Elyzha, Adhinda Nurr; Marsyal, Muhammad Guntur; Hardianto, Putra Ananda Nurrafi Feryansyah (Prodi Teknologi Pangan Fakultas Pertanian Universitas Islam Indragiri, 2024)
Fish is an economical food source and offers a more affordable alternative compared to beef and chicken. One of the commodities suitable as an inexpensive, easily found, and cultivated food with high protein value is tilapia. However, tilapia is perishable if not handled quickly or stored at low temperatures. To extend the shelf life of tilapia, processing is needed to maintain both the shelf life and the quality of the product, one of which is through fermentation. One traditional fermentation method frequently used by the people of South Sumatra is Bekasam. This study aims to determine the effect of the fermentation duration of Bekasam tilapia on its preference level or hedonic quality. Observations were made on days 3, 5, 7, 8, and 9 with organoleptic and hedonic tests on those days. The method used in this research is an experimental method. Non-parametric data from the organoleptic tests were analyzed using the Friedman test, followed by ANOVA. The parameters tested included pH, appearance, aroma, taste, and texture of Bekasam tilapia. The results showed that Bekasam tilapia with 3 days of fermentation provided the best results with a pH of 6.40, and the preference scores for appearance, taste, aroma, and texture were 5.00c, 4.33c, 5.91c, and 6.47c, respectively